Historiographical Conceptions in Lithuania - Gaigalaitė, Aldona (Problemos, 1970)
Lithuanian chronicles – “The Bichovco chronicle”, “Annals of the Great Lithuanian Principality”, “The Origin of the Lithuanian kin” are written under the influence of the Renaissance ideas and they differ from chronicles of other nations in their secular character. Ideas of the Enlightenment did not find an application in Lithuania. S. Daukantas, the first Lithuanian historian, worked in the early 19th century. His works are similar to those of the French romanticists. In the 19th century neoromanticism was widely spread in Lithuania. The spirit of romanticism contributed to dissemination of patriotism, to the struggle for the national language and culture. Under the rule of bourgeoisie Lithuanian historians were writing under obvious influence of positivism. At the same time both in the Soviet Union and U.S.A. Lithuanian Marxist historians began their activity. Marxist division into periods of the Lithuanian history was fixed according to so cia1-economic formations. Social and economic questions, problems of the revolutionary movement, the origin and the role of CP of Lithuania are being studied.